Evaluation and Challenges of Law Enforcement in the Implementation of the 2024 Election: A Case Study of Lebak Police - Aldika Martua Sitorus; Surya Nita; Chotib Chotib; Joshua Mualim; Agung Ikhssani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
As the world's third-largest democracy, Indonesia faces complex challenges in the execution of its elections, spanning logistics, security, and law enforcement. In practice, various challenges frequently arise in enforcing laws related to electoral violations. The Indonesian National Police (Polri), specifically the Lebak Police (Polres Lebak) in Banten, plays a crucial role in maintaining order and security throughout the election process. As a law enforcement agency, Polres Lebak is tasked with preventing, controlling, and addressing various forms of violations such as money politics, black campaigns, hoax dissemination, and violence during the campaign period and post-election. This study aims to analyze the challenges faced by Polres Lebak in maintaining the integrity and smooth operation of the 2024 elections and to assess the preventive measures and handling of election violations implemented by Polres Lebak. The article employs a qualitative analysis method supported by law enforcement theory. The findings reveal that Lebak Police faces complex challenges in ensuring the integrity and smoothness of the 2024 elections, including potential social and political conflicts, threats of money politics, hoax dissemination, as well as logistical preparedness and pressure from political actors. Given the broad and diverse socio-cultural landscape, Lebak Police needs to apply a comprehensive approach and coordinate with various parties to secure polling stations (TPS), prevent fraudulent practices, and manage limited human resources and technology. Measures include socializing election rules, establishing Integrated Law Enforcement Centers, monitoring money politics and disinformation, securing TPS, using technology to monitor violations, setting up patrols and security posts in vulnerable areas.